SOCIAL CAPITAL AND COMMUNITY ACCEPTANCE OF COVID-19 SURVIVORS IN ACEH - Maisarah, Siti (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2022)
The people of Aceh with their socio-cultural characteristics have strong social capital. This is a much needed potential to strengthen Covid-19 survivors in Aceh. Reality shows that strong social capital, in fact, has not played much of a role in strengthening covid survivors in Aceh Besar, it should be in this pandemic situation where the social nature of the community is getting stronger such as mutual cooperation, cooperation, mutual trust, mutual assistance and so on. But in reality, this pandemic outbreak is being faced against what it should be so that social capital weakens. The purpose of this study was to determine the relationship between social capital and public acceptance of Covid-19 survivors. There are two variables used in this analysis: social capital and public acceptance. The dependent variable is social capital and the independent variable is public acceptance. The type of research used is quantitative correlation. Data collection techniques using a questionnaire. To test the hypothesis using simple linear regression and correlation. The results showed that there was a relationship between social capital and public acceptance with a significance value of 0.000 (P<0.5) so it was stated that the correlation was stated. And there is a role for social capital on public acceptance, the higher the role of social capital, the higher the public acceptance of Covid-19 survivors. Keywords: Social capital, community acceptance and Covid-19 survivors